Innovative green material from nano-cellulose bio-plastic composite / Dr. Siti Norasmah Surip … [et al.] - Surip, Siti Norasmah; Bonnia, Noor Najmi; Azmi, Nur Naziha; Wan Jaafar, Wan Nor Raihan (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Bio-plastic known as polylactic acid (PLA) toughened by kenaf nano-cellulose green composite was produced due to lightweight material and its unique ability of bio-degradable. In this research, the effect of kenaf Nano-cellulose loading on the mechanical properties and thermal behaviour of composites were investigated. Kenaf Nano-cellulose and PLA pallets were extruded and compression molded according to ASTM standard of testing. PLA/kenaf Nano-cellulose green composites were manufactured for an alternative product in automotive, household's products and also medical devices. The products are environmental friendly, light weight, bio-degradable yet strong.